THE INFLUENCE OF SERVICE PERFORMANCE AND PASSENGER SATISFACTION ON PUBLIC TRANSPORT LOYALTY IN A SMALL CITY IN A DEVELOPING COUNTRY - Suryani, Fitrika Mita; Mutiawati, Cut Mutiawati; Faisal, Ruhdi (Journal of Applied Engineering Science, 2023)
Public transportation is widely considered more attractive in developed countries compared to developing countries, primarily due to its level of service performance, and the influencing factors vary depending on the characteristics of the place and the community. Meanwhile, passenger loyalty is essential to increase the demand for public transportation. This research aims to investigate the impact of service performance and passenger satisfaction on passenger loyalty to public bus transportation in Banda Aceh, Indonesia. The research was conducted on six Trans Koetaradja Bus corridors that connect the city and its surrounding areas, and the data was analyzed using the multiple regression method with SPSS. The results showed that that service performance and passenger satisfaction had an impact on passenger loyalty, with a correlation coefficient of 0.563. However, the determination value (R2) was only 0.317, indicating that only 31.7% of the service performance and passenger satisfaction affected passenger loyalty to the Trans Koetaradja bus. The remaining 68.3% were influenced by other variables. Meanwhile, the low contribution of service performance and passenger satisfaction was likely due to the fact that Trans Koetaradja passengers have private vehicles, which are considered more efficient. This can be seen from the respondents' trip frequency of only 1-2 times a week. To address this issue, integrated and accessible public transportation and mixed-use urban planning are needed in Banda Aceh to improve travel duration. It is hoped that these results can improve the public interest and loyalty to public transportation in their daily activities.
Keywords: service performance, passenger satisfaction, loyalty, public transportation, trans koetaradja